2015
DOI: 10.1596/1813-9450-7465
|View full text |Cite
|
Sign up to set email alerts
|

Dark Costs, Missing Data: Shedding Some Light on Services Trade

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Anderson and Van Wincoop (2004) discuss the difficulty of measuring and collecting reliable data on trade costs regarding trade in goods. For service trade, this becomes even more challenging, because trade costs for services are very specifically related to their industry characteristics (Anderson et al, 2015;Borchsenius et al, 2010;Francois & Hoekman, 2010). Since we 7 For instance, Kelle et al (2013) record that in 2005 only 85 out of 2,212 German service exporting firms chose Mode 3 as their export channel.…”
Section: Gravity Equation For Service Tradementioning
confidence: 98%
See 1 more Smart Citation
“…Anderson and Van Wincoop (2004) discuss the difficulty of measuring and collecting reliable data on trade costs regarding trade in goods. For service trade, this becomes even more challenging, because trade costs for services are very specifically related to their industry characteristics (Anderson et al, 2015;Borchsenius et al, 2010;Francois & Hoekman, 2010). Since we 7 For instance, Kelle et al (2013) record that in 2005 only 85 out of 2,212 German service exporting firms chose Mode 3 as their export channel.…”
Section: Gravity Equation For Service Tradementioning
confidence: 98%
“…This is mainly due to the higher volume of trade in goods, but also due to limited data availability for trade in services. Yet, in the last years more and more authors have shown that the standard gravity equation is also suitable for trade in services (e.g., Anderson et al, 2015;Ceglowski, 2006;Egger et al, 2012;Francois et al, 2007;Head et al, 2009;Kimura & Lee, 2006;Nordås, 2018;Walsh, 2006). However, the most difficult task for an analysis of trade relations is still the measurement of trade costs t ij .…”
Section: Gravity Equation For Service Tradementioning
confidence: 99%
“…The empirical strategy employed to convert the information in the STRI database into Ad Valorem Equivalents (AVEs) is based on a gravity model. Traditionally used to analyse patterns of trade in goods, gravity models have also been widely applied to cross-border trade in services (Eaton and Kortum, 2018;Nordas and Rouzet, 2017;Van der Marel and Shepherd, 2013;Anderson et al, 2015).…”
Section: Box 6 Computing Trade Costsmentioning
confidence: 99%
“…The empirical strategy employed to convert the information in the STRI database into AVEs is based on a gravity model, the workhorse model of the empirical trade literature. Traditionally used primarily to analyse patterns of trade in goods, gravity equations have also been widely applied to cross-border trade in services (Eaton and Kortum, 2018;Nordås and Rouzet, 2017;Van der Marel and Shepherd, 2013;Anderson et al, 2015). Formally, the gravity model can be expressed as follows:…”
mentioning
confidence: 99%